Soil Compaction by Valmet Forwarder Operation at Soil Surface with and without Slash - Juang Rata Matangaran (Jurnal Manajemen Hutan Tropika, 2012)
Soil compaction by machine used in forest harvesting operation caused negative impacts for regeneration and tree growth.  This research was intended to analyze the effectiveness of using slash to decrease soil compaction, to analyze soil compaction at various soil depths, and to measure rut depth at  soil surface.  Valmet 860.1 forwarder was used in this research. Soil compaction was measured through its bulk density, cone index, and rut depth, under the condition with and without slash.  The slash comprised of twigs, branches, and leaves as wastes from harvested Acacia mangium that were stacked to a width of about 1 meter in thickness following forwarder traffic. Results indicated that slash was effective in decreasing soil compaction.  About 50% increased in soil compaction by a Valmet forwarder could be reduced by using slash coverings at soil surface.  The maximum soil bulk density occurred after 5 forwarder passes.  Soil compaction also occurred at subsurface soil. After forwarder traffic, increasing cone index was observed at subsurface of various soil depths.  Slash was effective in decreasing soil compaction up to 20 cm in soil depth, although soil compaction by forwarder operation was slightly increased until 50 cm of soil depth.  Rut was not observed under the slash however rut of about 24 cm in depth was formed at soil surface without slash.  Using slash as coverings for forwarder operation reduced soil damaged. Keywords: soil compaction, forwarder Valmet, Acacia mangium, rutted, slash